The Concept Of Jarimah Hudud In The Qur'an - Achmad; Miftahul Ulum; Nasiri (STID Raudlatul Iman Sumenep, 2024)
The Qur'an is the word of Allah which was revealed to mankind as a guide in organizing life, so that humans can achieve happiness in life in this world and in the hereafter. In order for this to be achieved, the aim of the Islamic teachings is to protect and maintain religion, soul, lineage, intellect and property which are adh-dharuriyatal-khamsu (five urgent matters in human life). All actions that are prohibited by Allah SWT. and threatened with had and ta'zir punishments. Had is a criminal act and the criminal sanctions have been regulated in such a way in the texts of the Qur'an and Al-Hadith. According to Abdul Qadir Audah, there are seven types of hudud, namely: adultery, accusing of adultery, drinking wine, theft, khirobah, apostasy, and rebellion. There are verses explaining Hudud 9 times in the Qur'an in 5 letters, namely, 3 times in the QS. Al-Baqarah, 2 times in QS An-Nisa', 2 times in Surah At-Taubah, 1 time in Surah Al-Mujjadi, 1 time in Surah Ath-talak. all of them are classified as madaniyah. The conclusion from what I wrote is that Hudud is a limit that has been determined by Allah which cannot be violated and anyone who violates it will be subject to Hadd sanctions. These provisions have been regulated in the Nash Al-Qur'an and Hadith. Al-Qur’an adalah firman Allah yang diturunkan kepada umat manusia sebagai pedoman dalam menata kehidupan, agar manusia memproleh kebahagian hidup di dunia dan di akherat. Supaya hal tersebut tercapai, Tujuan pensyari’atan ajaran Islam adalah untuk menjaga dan memelihara agama, jiwa, keturunan, akal dan harta yang merupakan adh-dharuriyatal-khamsu (lima perkara mendesak pada kehidupan manusia).segala perbuatan yang dilarang oleh Allah swt. dan diancam dengan hukuman had dan ta’zir. Had adalah tindak pidana dan sanksi pidananya sudah diatur sedemikian rupa dalam nash Al-Qur’an dan Al-HadisMenurut Abdul Qadir Audah yang termasuk dalam jarimah hudud seban- yak tujuh macam, yaitu: zina, menuduh zina, peminum khamar, pencurian, khirobah, murtad, dan pemberontakan. Ayat-Ayat yang menerangkan Hudud dalam terdapat 9 kali dalam Al-Qur’an pada 5 surat yaitu, 3 kali dalam QS. Al-Baqarah, 2 kali dalam QS An-Nisa’, 2 kali dalam surat At-Taubah, 1 kali dalam surat Al-Mujadalah, 1 kali dalam surat Ath-talak. kesemuanya Tergolong madaniyah. Kesimpulan dari yang sy tulis adalah bahwa Hudud itu adalah batasan yang telah ditentukan oleh Allah yang tidak boleh dilanggar dan barng siapa yang melanggar, maka akan kenak Sanksi Had. Ketentuan itu telah diatur Dalam Nash Al-Qur’an dan Hadist.